ANALISIS GAYA BAHASA LAGU-LAGU IWAN FALS DALAM ALBUM 1980-1990 - bobok, arlyanto sonne; Hamsa, Akmal; Dj., Sulastriningsih (Fakultas Teknik Universitas Negeri Makassar, 2022)
This research is a qualitative research that aims to; (1) examining the style of language contained in Iwan Fals' songs on the 1980-1990 album; (2) examining the meaning of figurative language contained in Iwan Fals' songs on the 1980-1990 album; and (3) examine the relationship between the meaning of figurative language and educational values in Iwan Fals' songs on the 1980-1990 album. Data in the form of words, sentences or expressions that contain language styles. The data collection technique used is the documentation technique. Performance results; (1) the style of language used in Iwan Fals' songs on the 1980-1990 album, namely formal, informal, conversational, climax, antithesis, repetition, rhetorical, and figurative language styles; (2) the meaning contained in the style of language in the album songs of Iwan Fals 1980-1990, namely lexical, referential, connotative, contextual, associative meanings, terms, and proverbs; (3) the relationship between the songs of Iwan Fals' 1980-1990 album and educational values, which are related to the values of religious education, the values of moral education, and the values of social education.